Application of Molybdenum Carbide Catalysts for the CO2-assisted Oxidative Dehydrogenation of Ethane - Marquart, Wijnand (Department of Chemical Engineering, 2023)
The rising demand for light olefins is at present mainly met via catalytic/thermal dehydrogenation of alkanes at temperatures of up to 900 °C. Under these severe process conditions, competing side reactions and catalyst deactivation via coking are the major challenges. Co-feeding an oxidant significantly decreases the reaction temperature. The oxidative dehydrogenation of ethane to ethylene, using CO2 as the oxidant (CO2-ODH), has earned a lot of interest in the past decade. The use of CO2, a soft oxidant in comparison to O2, prevents the overoxidation reaction of the paraffin to CO2 and allows for improved heat control. Besides that, the coking effect, which is believed to be the main catalyst deactivation pathway during these high temperature processes, could be significantly lowered due to the reverse Boudouard reaction. The most common catalytic materials reported are reducible metal oxides (MOx) due to their redox properties; a key concept to activate the C-H bond of the alkane and subsequently activate CO2. Besides metal oxides, transition metal carbides have also shown to be active for the CO2-ODH, reaching high yields of ethylene. Specifically, molybdenum carbide (MoxCy) has shown to be a highly efficient catalyst for CO2 activation and alkane dehydrogenation, demonstrating its ability to cleave C-H bonds. These characteristics are important in making a MoxCy-based catalyst a serious candidate for the CO2- ODH of light alkanes. This work entails the design of novel MoxCy-based catalysts for application in the CO2-ODH of C2H6. Previous work on MoxCy-based catalysts found that the bulk material has limited activity and selectivity towards producing C2H4 but is significantly improved once dispersed on a support material. The type of support material dictates whether the CO2-ODH reaction takes place, or if one of the major side reactions, the dry-reforming of C2H6 to synthesis gas, is preferred. In this study, MoxCy nanoparticles were prepared via various (novel) synthesis techniques, dispersed on a variety of MOx support materials as well as modified with various promoters. Besides the exploratory nature of this study, gaining knowledge on the activity of the various formulations of MoxCy-based catalysts, the preparation conditions of the carbide materials were investigated. To prepare MoxCy, the precursor samples (in the molybdate or oxide phase) are exposed to a temperature programmed treatment (carburization) in the presence of a carbonaceous and reductive gas mixture. The carbide formation, in terms of crystallite structure, surface composition as well as potential fouling mechanisms is highly dependent on the heating rate, gas mixture, final temperature and precursor composition. Various experiments utilizing in situ characterization techniques, such as in situ X-ray diffraction, X-ray adsorption and Raman spectroscopy as well as online product analysis techniques were employed to gain knowledge on the carburization process, the structural and chemical properties and their effect on the activity of the various prepared catalysts in the CO2-ODH as well as the reverse water-gas-shift reaction. The use of MoxCy-based catalysts in the CO2-ODH reaction has not been thoroughly investigated in literature before and is still a very new topic to the scientific community. The presented research can contribute on various aspects of the use and viability of MoxCy-based catalysts in CO2 utilizing reactions and can be extended to dry-reforming or CO2 hydrogenation to fuels. In terms of catalyst synthesis, the extensive characterization exposing the various possible crystal structures of MoxCy nanoparticles and application of surface sensitive techniques, allowed for a better understanding of the possible active phases responsible for CO2 and alkane activation. Besides the identification of the active phase, the deactivation mechanism for MoxCy-based catalysts in the CO2-ODH reaction is studied in more detail by focusing on the crystal structure and the presence of carbon on the catalyst surface. By varying catalyst compositions as well as reaction conditions, including the use of various co-feeding experiments, an increase in catalytic stability, while maintaining high yields of the desired product from CO2-ODH (ethylene), was achieved.